Public-private knowledge transfer and access to medicines: a systematic review and qualitative study of perceptions and roles of scientists involved in HPV vaccine research - Jahn, Rosa; Müller, Olaf; Nöst, Stefan; Bozorgmehr, Kayvan (Globalization and health, 2020)
Public research organizations and their interactions with industry partners play a crucial role for public health and access to medicines. The development and commercialization of the Human Papillomavirus (HPV) vaccines illustrate how licensing practices of public research organizations can contribute to high prices of the resulting product and affect accessibility to vulnerable populations. Efforts by the international community to improve access to medicines have recognised this issue and promote the public health-sensitive management of research conducted by public research organizations. This paper explores: how medical knowledge is exchanged between public and private actors; what role inventor scientists play in this process; and how they view the implementation of public health-sensitive knowledge exchange strategies.
Gesehen am 26.03.2020